Parastasia oligomera — новый вид эвгленоидид из кишечника циклопов - Палиенко, Л.П. (Вестник зоологии, 1982)
The papercontains an illustrated description of Parastasia oligomera sp. n . from intestines of its host, Eucyclops serrulatus. From all known species of the genus it differs the by presence of only 16 daughter individuals on generative stage. From the closely related P. cyclopis it also differs by palintomic (instead of syntomic) division, by trophic stagebody size (160-190versus125 um), and by flagellate individuals size (29.33 versus 30-40 um).